Computer graphics dictionary - Stevens, Roger T. (Charles River Media, 2002)
The popularity of special effects movies and the video game industry has introduced thousands of new terms, techniques, and software applications to both the computing professional and the general user. Unfortunately, these graphics creations represent a convergence of expertise from several different subject areas, resulting in a lack of familiarity with many terms. This unique dictionary includes over 4,000 definitions and illustrations from the computer graphics world, including those from digital filmmaking, animation, programming, mathematics, holography, photorealism, lighting, character creation, game development, modeling, and more.